2019
DOI: 10.17512/jamcm.2019.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer analysis of non-Newtonian natural convective fluid flow using homotopy perturbation and Daftardar-Gejiji & Jafari methods

Abstract: In this paper, the analytical solution of natural convective heat transfer of a non-Newtonian fluid flow between two vertical infinite plates using the Homotopy Perturbation Method (HPM) and Daftardar-Gejiji & Jafari Method (DJM) is presented. The heat transfer problem of natural convection is observed in many engineering fields including geothermal systems, heat exchangers, petroleum reservoirs, nuclear waste reserves, etc. The problem which is modelled as fully coupled nonlinear ordinary differential equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A number of studies have been carried out to establish the strength of HPM by comparing the results obtained to other methods such as Adomian Decomposition Method (ADM) [12]. Remarkably, these studies have concluded that the method is more accurate and effective than ADM. Other studies carried out with the homotopy perturbation method (HPM) include its use for the analysis of heat transfer in longitudinal fins [13], the use of HPM and collocation method (CM) for analysis of thermal performances of porous fin with temperature-dependent heat generation [14] and heat transfer analysis of non-Newtonian natural convective fluid flow using homotopy perturbation and Daftardar-Gejiji and Jafari methods [15].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been carried out to establish the strength of HPM by comparing the results obtained to other methods such as Adomian Decomposition Method (ADM) [12]. Remarkably, these studies have concluded that the method is more accurate and effective than ADM. Other studies carried out with the homotopy perturbation method (HPM) include its use for the analysis of heat transfer in longitudinal fins [13], the use of HPM and collocation method (CM) for analysis of thermal performances of porous fin with temperature-dependent heat generation [14] and heat transfer analysis of non-Newtonian natural convective fluid flow using homotopy perturbation and Daftardar-Gejiji and Jafari methods [15].…”
Section: Introductionmentioning
confidence: 99%